Co-creating value in organisations with ITIL 4. - Limited, TSO. (London : The Stationery Office Ltd, 2021)
Co-creating value in organizations with ITIL 4 explores how to achieve value across multiple business models using ITIL 4 at different stages of business and product evolution.
9.6 In summary -- Chapter 10: The value of peeking under the cover -- 10.1 Measuring success -- 10.2 Fragile services -- 10.3 Balancing dependencies -- 10.4 A fragile case study (personal story) -- 10.5 In summary -- Chapter 11: One language -- Chapter 12: The end - or just the beginning? -- Glossary -- Further research -- Notes.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books